Optimization of GDL to improve water transferability. (December 2021) - Li, Tianya; Wang, Kejian; Wang, Jihao; Liu, Yueqi; Han, Yufen; Xu, Zhiyang; Lin, Guangyi; Liu, Yong
Abstract: As a rising star, the fuel cell will be applied very broadly. However, when the fuel cell works at a high current, too much water yield and the redundancy water block the air or oxygen enter the fuel cell, then the power reduces sharply. The gas diffusion layer (GDL) in the fuel cell is the critical component to transfer water and gas. A novel GDL was prepared in this paper to improve transferability. The new GDL consists of one carbon paper and two microporous layers. The microporous layer close to carbon paper is modified by pore-former CaCO3 . The total thickness of the new GDL is 270 μm; then, the samples were pressed to 220, 240, and 260 μm by rolling, respectively. The electrochemical impedance spectroscopy tests at a large current (2.5 A/cm 2 ) show that the fuel cell with 240 μm GDL has relatively small transmission impedance regardless of high or low humidity. The results show that the new GDL can significantly improve the water transferability of the proton exchange membrane fuel cell.